Analysis of protein import into chloroplasts isolated from stressed plants - Ling, Q; Jarvis, P (Journal of Visualized Experiments, 2016)
Chloroplasts are organelles with many vital roles in plants, which include not only photosynthesis but numerous other metabolic and signalling functions. Furthermore, chloroplasts are critical for plant responses to various abiotic stresses, such as salinity and osmotic stresses. A chloroplast may contain up to ~3000 different proteins, some of which are encoded by its own genome. However, the majority of chloroplast proteins are encoded in the nucleus and synthesized in the cytosol, and these proteins need to be imported into the chloroplast through translocons at the chloroplast envelope membranes. Recent studies show that the chloroplast protein import can be actively regulated by stress. To biochemically investigate such regulation of protein import under stress conditions, we developed the method described here as a quick and straightforward procedure that can easily be achieved in any lab. In this method, plants are grown under normal conditions and then exposed to stress conditions in liquid culture. Plant material is collected, and chloroplasts are then released by homogenization. The crude homogenate is separated by density gradient centrifugation, enabling isolation of the intact chloroplasts. Chloroplast yield is assessed by counting, and chloroplast intactness is checked under a microscope. For the protein import assays, purified chloroplasts are incubated with 35S radiolabeled in vitro translated precursor proteins, and time-course experiments are conducted to enable comparisons of import rates between genotypes under stress conditions. We present data generated using this method which show that the rate of protein import into chloroplasts from a regulatory mutant is specifically altered under osmotic stress conditions.